2021
DOI: 10.1007/s41207-021-00246-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing climate change impacts on crops by adopting a set of crop performance indicators

Abstract: The impact of climate change on the agricultural systems of three major islands in the Mediterranean basin, namely Sicily, Crete and Cyprus, was evaluated using a suite of specifically calibrated crop models and the outputs of a regional circulation model for Representative Concentration Pathway (RCP) 4.5 and 8.5 downscaled to 12 km of resolution and tested for its effectiveness in reproducing the local meteorological data. The most important annual (wheat, barley, tomato and potato) and perennial (grapevine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
3
8
0
Order By: Relevance
“…In addition, this early sowing allows the flowering stage to take place between the period from the end of February until the beginning of April, which allows the Mexicali cultivar's plant to avoid the high temperaturesin May and June. These results are compatible with those of [59], who also predicted the adaptation of wheat to early sowings in 2031-2060 climate conditions, under both RCP 4.5 and RCP 8.5 scenarios in the Mediterranean area. However, late sowing in mid-November and mid-December resulted in poor yields, as they led to the achievement of the durum wheat's flowering and grain-filling stages through the high-temperature period of the mid-April and early June period, which induce durum wheat's grain yield losses by scalding.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, this early sowing allows the flowering stage to take place between the period from the end of February until the beginning of April, which allows the Mexicali cultivar's plant to avoid the high temperaturesin May and June. These results are compatible with those of [59], who also predicted the adaptation of wheat to early sowings in 2031-2060 climate conditions, under both RCP 4.5 and RCP 8.5 scenarios in the Mediterranean area. However, late sowing in mid-November and mid-December resulted in poor yields, as they led to the achievement of the durum wheat's flowering and grain-filling stages through the high-temperature period of the mid-April and early June period, which induce durum wheat's grain yield losses by scalding.…”
Section: Discussionsupporting
confidence: 91%
“…In general, the main mechanisms controlling the simulated wheat responses are the direct and indirect temperature effects on the wheat's phenological development. It is well known that warmer temperatures accelerate the plant growing cycle through advanced anthesis and maturity, thus resulting in smaller biomass accumulation and lower yields [7,43]. Several reports have noted the detrimental impact of extreme weather events and climate change on wheat productivity in the Mediterranean and Asian countries [44][45][46].…”
Section: Long-term Grain Yield and Biomass Simulationmentioning
confidence: 99%
“…This trend might be explained by the precocity of 'Karim' compared to 'Salim' (Table S2). Several authors pointed out that the use of wheat cultivars with a shorter growing cycle and early flowering can escape extreme climate events and thus result in a winning strategy for higher yields [7,52]. In contrast, Asseng et al [53] indicated that a prolonged vegetative growth may better compensate for the reduced growing season length induced by higher temperatures.…”
Section: Site Description and Meteorological Data Collectionmentioning
confidence: 99%
“…Olive tree cultivation is one of the most important agricultural systems in Italy, extending over more than 1 million ha and mainly concentrated in the southern and central regions [1]. Despite its economic and environmental relevance, this cultivation is currently threatened by climate change [2][3][4][5] and hampered by the lack of modern agronomic management strategies, favoring the progressive abandonment of olive groves [6,7]. By contrast, the recovery of this cultivation over abandoned areas and an increase in the productive potential of marginal olive groves could enhance farmers' income and contribute to preserving and maintaining the rural landscape (CATChCO2-live project, 2017).…”
Section: Introductionmentioning
confidence: 99%